The Great Proletarian Cultural Revolution, Disruptions to Education, and the Returns to Schooling in Urban China - John T. Giles; Albert Park; Meiyan Wang (Institute for the Study of Labor (IZA), 2015)
This paper provides new evidence on educational disruptions caused by the Cultural Revolution and identifies the returns to schooling in urban China by exploiting individual-level variation in the effects of city-wide disruptions to education. The return to college is estimated at 49.8% using a conventional Mincer-type specification and averages 37.1% using supply shocks as instruments and controlling for proxies for ability and school quality, suggesting that high-ability students select into higher education. Additional tests show that the results are unlikely to be driven by sample selection bias associated with migration or alternative pathways through which the Cultural Revolution influenced adult productivity.
Keywords: I20; J24; J30; O15; O53; 330; returns to schooling; wages; education; China